Implementasi Webinar Trading dalam Meningkatkan Edukasi Masyarakat di PT Agrodana Futures Surabaya - Ria Istanti, Wike; Bhirawa Dwi Atma Citalada, Muhammad (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Futures trading is an important part of the modern investment ecosystem. This activity involves significant risks and requires a deep understanding of market dynamics and risk management. Poor investment choices and large financial losses are often caused by a lack of financial literacy and negative perceptions of the futures trading industry in Indonesia. Most consumers find it difficult to understand basic concepts such as margin, leverage, and risk management due to the popularity of speculative activities and a lack of understanding about the legality of brokers. The objective of this community service activity is to improve and empower public trading literacy by utilizing webinars as an interactive and accessible digital learning tool. The method used is qualitative descriptive through the organization of the “Ruang Trading 2025” webinar, which featured speakers from PT Agrodana Futures, ICDX, and ASPEBTINDO. The results of this activity showed a significant increase in participants' understanding of risk identification, the use of stop loss and take profit strategies, and the ability to distinguish between legal and illegal brokers. It is estimated that this initiative will develop into a successful digital education model to create a safer, more transparent, and sustainable futures trading ecosystem for the wider community.